Implementasi Sistem Informasi Akuntansi untuk Perusahaan Garmen XYZ - Joshua Ronaldo Citra; Rinabi Tanamal (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2019)
Nowadays in Indonesia, the company needs toward information system is an absolute thing. Information System has become one of the components in a company. There are many positive advantages obtained in using information system. Information system has many types such as Accounting Information System (AIS) supporting the accounting in company. XYZ is an company engaged in garment in Surabaya. As a company, it has business processes related to accounting. To support the accounting process in XYZ company, it needs an accounting application. Accurate is an application providing AIS service created by CPSSoft. Accurate is chosen because the use is simple and it provides modules which support business process of companies. The problem faced by XYZ company in this research was how to arrange Accounting Information System in XYZ company using Accurate application and to overcome the problems. Thus, there would be some activities. First was interview and observation of business process in XYZ. The second was data transfer from the previous application to Accurate. The third was installment and training the Accurate to the staffs and the owner of XYZ company. Accurate could ease business process and enhance staff performance and the owner of company.